Clinical and molecular characterization of neonatal diabetes and monogenic syndromic diabetes in Asian Indian children. (20th August 2012) - Jahnavi, S; Poovazhagi, V; Mohan, V; Bodhini, D; Raghupathy, P; Amutha, A; Suresh Kumar, P; Adhikari, P; Shriraam, M; Kaur, T; Das, AK; Molnes, J; et al.
Abstract : Mutations in the pancreatic ATP sensitive K + channel proteins [sulfonyluea receptor 1 (SUR1) and inward rectifier K + channel Kir6.2 (Kir6.2), encoded by ATP‐binding cassette transporter subfamily C member 8 ( ABCC8 ) and potassium channel J11 ( KCNJ11 ), respectively], are the most common cause of neonatal diabetes. We describe the clinical presentation and molecular characterization of Asian Indian children with neonatal diabetes mellitus and monogenic syndromes of diabetes. We sequenced KCNJ11, ABCC8 and insulin ( INS ) genes in 33 unrelated Indian probands with onset of diabetes below one year of age. A total of 12 mutations were identified which included ABCC8 mutations in seven, KCNJ11 mutations in three and INS mutations in two children. The Asp212Tyr mutation in ABCC8 was novel. We also detected two novel mutations (Val67Met and Leu19Arg) in children with syndromic forms of diabetes like Berardinelli Seip syndrome [1‐acyl‐ sn ‐glycerol‐3‐phosphate acyltransferase beta ( AGPAT2 )] and Fanconi Bickel syndrome [solute carrier family 2A2 ( SLC2A2 )]. Children carrying the KCNJ11 (Cys42Arg, Arg201Cys ) and ABCC8 (Val86Ala, Asp212Tyr) mutations have been successfully switched over from insulin therapy to oral sulfonylurea. Our study is the first large genetic screening study of neonatal diabetes in India.